Operationalizing age-friendliness in urban China: a multi-case study of gated retirement and open multi-generational communities - Tan, Yiting; Huang, Jianyuan (Frontiers in Public Health, 2025)
BackgroundAge-Friendly Communities (AFCs) play a pivotal role in creating supportive social and physical environments, which enable older adults to maintain mobility, independence, healthier living, and successful aging-in-place.MethodsThis study employed a multi-case study method to analyze six comunities and two age-friendly community models in China: Gated Retirement Communities (GRCs) and Open Multi-Generational Communities (OMGCs), which have exhibited different effects in practice. An analytical framework incorporating policies, facilities, services, intergenerational relationships, and sustainability has been established to systematically compare these models, with the aim of identifying some more effective age-friendly measures at the community level.ResultsThe research results revealed that GRCs were prone to spatial inequality, idle waste of resources, violation of service commitment, intergenerational exclusion and unsustainability. On the contrary, OMGCs demonstrated better age-friendliness and stronger vitality.ConclusionOMGCs are more supportive and age-friendly than GRCs. Some key priorities and effective measures for the development of AFCs have been obtained from these communities, offering valuable insights for Asian nations and developing countries seeking to advance age-friendly initiatives.